Implementing Character Education Based on Local Wisdom in a Public Islamic Elementary School - Mansur, Mansur; Sholeh, Makherus (Journal of Integrated Elementary Education, 2024)
This study centers on implementing Character Education based on Local Wisdom at Public Islamic Elementary School 4 Banjar. It highlights the indispensable role of educators in imparting character values to students through local culture and wisdom. The research aims to grasp how Character Education based on local wisdom is practiced at Public Islamic Elementary School 4 Banjar Sungai Lulut and the factors that either facilitate or hinder its implementation. Employing a qualitative approach with a descriptive method, the study examines the activities and execution of Character Education based on local wisdom, involving teachers and students as research subjects. Data collection techniques encompass observation, interviews, and documentation, while data analysis involves data reduction, presentation, and conclusion. The findings demonstrate that the school effectively integrates local wisdom into Character Education through activities such as adopting the 5S culture (smile, greeting, greeting, politeness, and politeness), religious practices, sports, and scouting, all contributing to student character development. Supportive factors such as adequate facilities, the active role of teachers, parental involvement, and the inclusion of character education in the school curriculum further enhance the implementation. Conversely, inhibiting factors such as students' lack of awareness and insufficient facilities and infrastructure present challenges to the process. These findings hold practical implications for educators, researchers, and policymakers interested in character education and implementing local wisdom in elementary schools.